Mapeamento e análise dos processos secretariais das unidades acadêmicas da Universidade Federal do Pará, Campus Universitário Belém - PAES, Raul Vitor Oliveira (Universidade Federal do Pará, 2018)
In this Master Thesis, it´s intend to analyze the secretarial processes of Academic Departments of Para Federal University (UFPA), about the techniques of processes’ mapping. It stands out the present time when the Higher Federal Education Institution (HFEI) are in the adopt process the management technologies for the Federal Government, across the law and the experiences the adoption these technologies for the HFEI to optimize organizational and final processes. In contrast, with a globalization and a development of Communication and Information Technologies (CIT), beyond of own organizational technologies enables a development of actions linked a management and mapping processes in a public and private organizations. From this perspective, the following question is proposed: which processes can be improved in Executive Secretaries of University Campus of Belem in a Para Federal University? The theoretical context is substantiated in readings about a management and mapping processes and Secretariat, with focus in HFEI. Next, the methodologies’ procedure involved in an approach eminently qualitative, with exploratory and descriptive level, with case study classification. Already the collect data procedures are based in survey as of semi-structured focus group, applying questionnaires and structured interviews, in three moments, for attend objectives of identifying, prioritizing, mapping and improvement of secretarial processes, according proposal the research. And, in relation of analyze data techniques, were adopted combined techniques of content analysis and data triangulation, because of characteristics of interviews stages attend in a work, with representations through construction of processes’ maps by means of BPMN notation, own of mapping processes. The results pointed for an identification of nine secretarial processes developed for Executive Secretaries of Institutes and Centers of University Campus of Belem, with emphasis of prioritizing in three processes: General Direction Advisory, Documents’ Management and Public Service, with corresponding descriptions as of process maps and improvement proposal for each process. As conclusion, can infer there are own process of advisory area, with relation in a practice with other areas and exists differences between descriptions of processes, contrasting Departments, it demands special attention at the mapping moment. Because the differences, also is perceptive pointed the possibility more one proposal of process improvement, considering the particularity between the functional areas. Another conclusion pointed is a mapping processes contribute for an identification the workflows relations and products delivered intending permitting, thus, an effective diagnosis of activities and verifying points can be improved for achieve the support and organizational objectives, it permits ramifications for future studies and applications.